Castigo y exclusión en Ecuador desde la teoría criminológica crítica (Tema Central) - Echeverría Andrade, María Fernanda (2022)
The present contribution of criminological theory undertakes the search for understanding how at present the entire society that becomes in jail. For this purpose, the work theoretically and empirically investigates the massacre that occurred in Ecuador in February 2021. The death, suffering and exclusion produced in the largest prison massacre in the country are justification for inquiring about the causes and consequences derived from institutionalized violence. As a methodology, the case study is applied within a qualitative approach which allows us to get closer to the punitive violence deployed in prisons, to then propose an alternative and critical path regarding the treatment that is given to people in the context of confinement. This is how the proposal for the humane treatment of vulnerability is formulated in the last section, which stands as an unfinished solution but which can be helpful in mitigating the effects of imprisonment that affects prisoners, their families and relatives. Therefore, we begin to analyze the effects of punitive expansionism. Then the consequences of such expansionism are empirically revealed, and, finally, a proposal is developed dialectically to contain the punitive power which when it overflows, ends in massacre.